(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The article deals with the principles of marketing activity and its organization, methods of studying the demand and supply of specialists, the conditions for the organization of the specialist market, the use of marketing services in educational institutions and programs for its development, the formation of the image of an educational institution, the organizational and psychological possibilities of advertising in the organization of educational services. the word goes.